Collaborative engineering among designers with different preferences: Application of the preference set–based design to the design problem of an automotive front-side frame. (December 2013) - Inoue, Masato; Nahm, Yoon-Eui; Tanaka, Kenji; Ishikawa, Haruo
The advancement of computer networks and information technologies has been rapidly changing the manufacturing environment of the industrial age to that of the current information era. The engineering philosophy has been shifted from concurrent engineering to collaborative engineering among the respective areas of expertise in a design space. Handling uncertainties in an initial design process is of great importance, particularly for collaborative engineering. For collaborative engineering, designers having different preferences in the different disciplines need to represent their own possible design solutions or design solution spaces, and they also need to understand the other designers' design solution spaces. We have proposed a preference set-based design method that enables a flexible and robust design under various sources of uncertainties, while capturing a designer's preference. In this study, the proposed method was applied to a real industrial multi-objective design problem (i.e. an automotive front-side frame design). This study discusses the suitability of our proposed approach for obtaining the multi-objective satisfactory solutions that reflect the different design preferences of different designers in their design solutions for collaborative engineering.